2022
DOI: 10.1038/s41398-022-01999-7
|View full text |Cite
|
Sign up to set email alerts
|

Acid sphingomyelinase/ceramide system in schizophrenia: implications for therapeutic intervention as a potential novel target

Abstract: Schizophrenia is a severe mental illness, as the efficacies of current antipsychotic medications are far from satisfactory. An improved understanding of the signaling molecules involved in schizophrenia may provide novel therapeutic targets. Acid sphingomyelinase (ASM) catalyzes cellular membrane sphingomyelin into ceramide, which is further metabolized into sphingosine-1-phophate (S1P). ASM, ceramide, and S1P at the cell surface exert critical roles in the regulation of biophysical processes that include prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…In our previous study, we demonstrated a decrease in ASMse activity in the blood of MSA patients [ 16 ]. Interestingly, a recent review discussed the abnormalities of the ASMase–ceramide signaling pathway in SCZ patients [ 45 ]. This review discusses that the aberrations in the ASMase/ceramide system, especially ASMase activity and the levels of ceramide, may alter the cerebral microdomain structure and neuronal metabolism, leading to neurotransmitter dysfunction as dopamine neurotransmission and neuroinflammation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we demonstrated a decrease in ASMse activity in the blood of MSA patients [ 16 ]. Interestingly, a recent review discussed the abnormalities of the ASMase–ceramide signaling pathway in SCZ patients [ 45 ]. This review discusses that the aberrations in the ASMase/ceramide system, especially ASMase activity and the levels of ceramide, may alter the cerebral microdomain structure and neuronal metabolism, leading to neurotransmitter dysfunction as dopamine neurotransmission and neuroinflammation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, earlier research has described a broad range of neurological manifestations also for NPD including severe ataxia, cognitive deficits, and psychiatric disorders [ 46 ]. Zhuo and coauthors suggested that normalization of the aberrant ASMase/ceramide system or ceramide reduction using approved functional inhibitors of ASMase, such as fluvoxamine and rosuvastatin, may improve clinical outcomes of SCZ patients [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peripherally, aberrant alterations in sphingomyelin and ceramide levels in the red blood cells and skin are strongly linked to schizophrenia [ 50 ]. It has even been hypothesized that the disruption of the acid sphingomyelinase/ceramide system contributes to the dopamine neurotransmission malfunction, neuroinflammation, and oxidative stress, which are the main theories regarding the cause of schizophrenia [ 12 ]. Interestingly, PSAP plays a fundamental role in the sensitization of neurons to oxidative stress [ 8 ], and PGRN is also a neuroinflammation modulator [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSAP mutations are linked to Parkinson’s disease (PD) [ 10 ], and an association of single nucleotide polymorphisms (SNPs) in the PSAP gene with schizophrenia was revealed in a Dutch population [ 11 ]. Meanwhile, as the main substrate of saposins, sphingolipid metabolism is abnormal in patients with schizophrenia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This reduction shown in other studies was speculated to be the result of SCZ-associated upregulation in S1P-degrading enzymes genes. ( 45 )…”
Section: Implications Of Sm Deficit In Brain Disordersmentioning
confidence: 99%